Pengelolaan Pembelajaran IPS Dengan Memanfaatkan LingkunganSekolah Sebagai Sumber Belajar Di SMP Negeri 4 Ampel Satu Atap Boyolali - Budianingsih, Niken; , Prof. Dr. Bambang Sumardjoko; , Dr. Sofyan Anif, M.Si (2015)
The purpose of this study was to describe the social studies lesson plan to utilize the school environment as a learning resource in SMP Negeri 4 Ampel Satu Atap Boyolali. Describing the implementation of the social studies learning by utilizing the school environment as a learning resource in SMP Negeri 4 Ampel Satu Atap, Boyolali. Describe the process of evaluation of learning by utilizing IPS school environment as a learning resource in SMP Negeri 4 Ampel Satu Atap, Boyolali. The research is a qualitative research design ethnographic research. The location study performed at SMP Negeri 4 Ampel Satu Atap, Boyolali. Pengumplan engineering data using in-depth interviews, documentation, and observation. Analysis of the data by using three stages: data reduction, data presentation, and drawing conclusions with verification. The results showed that the learning plan IPS by using the school environment as a learning resource is organized into Learning Implementation Plan (RPP), with reference to the educational unit level curriculum (SBC), is one unit with the use of other learning resources, which is used as a reference implementation Learning includes: identity, learning objectives, learning materials, teaching methods, measures of learning activities, resources and media learning, and assessment. Implementation of social studies learning by making use of the school environment as a learning resource is done with reference to the RPP are predetermined, for 4 hours / week, is scheduled once every semester, with reference to the educational calendar, specifically the standard of competence and a certain basic competence. IPS evaluation of learning by utilizing the school environment as a learning resource implemented in a comprehensive manner with other basic competencies, the evaluation can be done through testing and non-testing. Evaluation in the form of tests carried out in writing in the form of daily tests, midterm repetition, repetition rise in class and school exams.